Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Belanja Modal di Kabupaten/Kota Provinsi Sumatera Utara - Eve Ida Malau; Calen Calen; Victor Marudut Mulia Siregar; Kharisma Yudha Saragih (Owner : Riset dan Jurnal Akuntansi, 2020)
The objective of the research was to analyze the influence of original local revenue and balance funds partially on the capital expenditure in districts / towns of North Sumatra Province. The amount of capital expenditure for each region varies according to the size of the region and the needs of the region. The realization of capital expenditure in each region can show the economic progress of a region. Based on data that the author obtained from the website of the Director-General of Fiscal Balance, there is still a capital expenditure budget that has not been maximally realized for regional development The population was 33 districts / towns of North Sumatra Province years of 2010-2018 and population will be used as sample. The data were processed by using panel data regression statistical method. The result of the research that original local revenue and balance fund had positive and significant influence on the capital expenditure in districts / towns of North Sumatra Province.